1994
DOI: 10.1071/ar9940321
|View full text |Cite
|
Sign up to set email alerts
|

Metallothionein and trace element metabolism in sheep tissues in response to high and sustained zinc dosages. 2. Expression of metallothionein m-RNA

Abstract: Increased dietary zinc (Zn) influences metallothionein (MT) expression in sheep, which in turn effects changes in the regulation of both Zn and copper (Cu) tissue uptake. Romney wether sheep were given ZnO on a regular basis, as required in protocols for the treatment of facial eczema, at either 12 g ZnO fortnight-1 or 12 g ZnO week-1, and the effect of Zn on MT-Ia and -II mRNA expression in liver, kidney, duodenal, muscle and skin tissue was compared with those of untreated animals. Tissue concentrations of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…In sheep, one study (Lee et al . 1994) found a significant increase in muscle Zn in response to herbage Zn, while in another Henry et al . (1997) reported a decrease.…”
Section: Nutritionmentioning
confidence: 90%
See 2 more Smart Citations
“…In sheep, one study (Lee et al . 1994) found a significant increase in muscle Zn in response to herbage Zn, while in another Henry et al . (1997) reported a decrease.…”
Section: Nutritionmentioning
confidence: 90%
“…In depletion studies in pigs (Shaw et al 2002;Hern谩ndez et al 2008), muscle Zn concentrations remained unchanged, while liver and kidney Zn were depleted. Supplementation with varying forms of Zn in cattle (Malcolm-Callis et al 2000;Kessler et al 2003), sheep (Lee et al 1994;Rojas et al 1995;Henry et al 1997) and chickens (Bou et al 2004(Bou et al , 2005 had little effect. In sheep, one study (Lee et al 1994) found a significant increase in muscle Zn in response to herbage Zn, while in another Henry et al (1997) reported a decrease.…”
Section: Zincmentioning
confidence: 99%
See 1 more Smart Citation
“…However, while Zn fed to sheep reduced the net accumulation of Cd in liver, it increased accumulation in kidney (Lee et al 1991;Rounce et al 1998). The accretion of Cd in the kidneys with high Zn doses has been associated with increased MT synthesis, which improved the effi ciency of the kidney to sequester Cd (Bremner 1978;Lee et al 1994;Peterson and Mercer 1988).…”
Section: Cadmium and Fluorine Intake And Distribution In Livestockmentioning
confidence: 99%